Pendekatan Syariah dalam Inovasi Pemasaran Produk Halal untuk Meningkatkan Loyalitas Pelanggan - Pujianto, Anang Bambang; Sarifiyono, Aggi Panigoro; Purnama, Susan; Sinaga, Johnson (Masoem University, 2025)
The rapid growth of the halal market and the increasing awareness of Muslim consumers towards products that comply with sharia principles make innovation in halal marketing a strategic issue. The urgency of this research lies in the need to answer the challenges of the halal industry in combining marketing innovation with a sharia approach to increase customer loyalty. This study aims to analyze the effect of sharia-based halal product marketing innovation on customer loyalty, as well as identify the main factors that influence consumer engagement. The method used is quantitative with a survey approach. A sample of 171 respondents was obtained through purposive sampling technique, with a measuring instrument in the form of a 5-point Likert scale questionnaire. Data were analyzed using multiple linear regression and Structural Equation Modeling (SEM) to test the causal relationship between variables. The results of the analysis show that all indicators in the questionnaire are valid (r> 0.739) and reliable (Cronbach's Alpha = 0.9789). The regression model shows an R² value of 0.9336, which means that 93.36% of the variation in customer loyalty can be explained by sharia-based halal marketing innovation. SEM confirms the significant influence of halal product innovation on loyalty (path coefficient = 0.52; p = 0.001) and sharia approach on loyalty (path coefficient = 0.47; p = 0.001). Theoretically, this study strengthens Dick and Basu's (1994) concept regarding value-based loyalty and extends Teece's (2007) application of marketing innovation in the halal context. Practically, the results of this study provide guidance for halal business actors to integrate sharia values ??such as honesty, transparency, and ethics in marketing innovation in order to build long-term loyalty. The novelty of this study lies in the combination of sharia approach and marketing innovation in one empirical model that is statistically tested in the context of the Indonesian halal market